Access to renal transplantation and post-transplantation prognosis (ReTRAPP) study of adults in Malaysia / Peter Gan Kim Soon - Peter Gan , Kim Soon (2020)
Introduction Renal transplantation (RT) is recognised as the preferred treatment modality for end-stage renal disease. However, Malaysian transplantation rates have been low compared to other countries. Numerous clinical determinants have been associated with renal transplant recipient' (RTRs) health, which is the main focus of the healthcare fraternity. Coincident with the rising interest for equitable healthcare, many studies in the high-income countries have examined the disparities in RT. On the contrary, little is known about the association of socioeconomic gradient of RTRs on the access and outcome of RT in Malaysia, a low- and middle-income country. ReTRAPP was designed to explore the factors that limit access as well as assess the association of socioeconomic status (SES) on the access and outcome (survival rate, quality of life and financial burden) of RT. Methodology Collection of qualitative data involved semi-structured interviews with eight keyinformants, who are identified by detailed stakeholder analysis. Their responses were used to explore current RT policy and service availability and to identify relevant themes. Quantitative data examined from the National Renal Registry of Malaysia for RTRs above 18 years between 2002 and 2011 (n=1234 recipients).Cox's regression was used to evaluate the association of SES on access to RT and post-transplantation survival rate. iv A quantitative study using a survey was administered to 409 RTRs in 6 public health facilities in Greater Kuala Lumpur. Linear regression was used to determine the association of SES on quality of life and logistic regression for association of SES and catastrophic health expenditure (CHE). Results The in-depth interviews are categorised and described by the socio-ecological model, which provided a framework better to understand the barriers and solutions to RT in Malaysia. Results from the thematic analysis illustrate a complex interplay of personal, cultural, and environmental factors. Lower household income was associated with reduced access to renal transplantation (adjusted PTrend = 0.001). Additionally, patients with higher educational attainment have a better survival rate post-transplantation (adjusted PTrend < 0.001). Mean scores for all WHOQOL domains were reduced for RTRs with low SES compared to high SES. After multivariable adjustment, educational attainment and household income continued to affect all WHOQOL domains significantly. 22.7% of RTRs experience CHE due to post-transplantation care. Household income is the only SES indicator to show statistical significance with Middle 40% household income group and Bottom 40% household income group having 4.7 times and 5.3 times more risk for CHE. v Conclusion ReTRAPP was conducted to explore the barriers that limit RT and evaluate the social inequalities in access and outcome of RT. Specific barriers and solutions highlighted in ReTRAPP indicate a need for policy change in the health service delivery model to improve the RT rate. ReTRAPP further highlights the disparities in access and post-transplantation care of RTRs. These findings provide healthcare leaders with opportunities to reduce disparities through a better understanding of the delivery of care. Considering the impact of socioeconomic differentials on disparities in healthcare, a multidiscipline partnership from various stakeholders is necessary to address the socioeconomic inequality in access to care and health outcomes for RTRs. Keywords Renal Transplantation, Socio-Economic Status, Access to Renal Transplantation, Outcome of Renal Transplantation, Malaysia